Fractional CO2 Laser Resurfacing Complications - Ramsdell, William M. (Seminars in Plastic Surgery, 2012)
Fractionated CO2 laser technology has allowed physicians to resurface patients with a lower rate of complications than nonfractionated ablative laser treatment. Unfortunately, adverse effects can still occur even with the best technology and physician care. Complication prevention, detection, and treatment are an important part of a physician's ability to provide the best result when treating a patient with fractionated CO2 resurfacing.
Keywords: complication; infection; scar; dyschromia